2014
DOI: 10.1016/j.bbagen.2013.08.024
|View full text |Cite
|
Sign up to set email alerts
|

Structure–function relationships of the peptide Paulistine: A novel toxin from the venom of the social wasp Polybia paulista

Abstract: The peptides Paulistine and Acm-Paulistine may be used as interesting tools to investigate the mechanisms of pain and inflammation in future studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 40 publications
3
8
0
Order By: Relevance
“…By combining MALDI-TOF MS with chromatographic separation, we have shown that the Odontomachus haematodus venom peptidome is composed of more than 100 small and linear peptides in the 700-3000 m/z mass range. This feature is consistent with a previous study on the venoms of five Neotropical Odontomachus species as well as wasp and cone snail venoms which are usually comprised of peptides with fewer than 35 residues (Baptista-Saidemberg et al 2011; Cologna et al 2013;de Souza et al 2004;Gomes et al 2014;Johnson et al 2010;Lewis et al 2012;Orivel et al 2001). In contrast, spider, scorpion and snake venoms may also contain larger peptides with typically from 30 to 100 amino acids (Olivera et al 1990).…”
Section: Discussionsupporting
confidence: 91%
“…By combining MALDI-TOF MS with chromatographic separation, we have shown that the Odontomachus haematodus venom peptidome is composed of more than 100 small and linear peptides in the 700-3000 m/z mass range. This feature is consistent with a previous study on the venoms of five Neotropical Odontomachus species as well as wasp and cone snail venoms which are usually comprised of peptides with fewer than 35 residues (Baptista-Saidemberg et al 2011; Cologna et al 2013;de Souza et al 2004;Gomes et al 2014;Johnson et al 2010;Lewis et al 2012;Orivel et al 2001). In contrast, spider, scorpion and snake venoms may also contain larger peptides with typically from 30 to 100 amino acids (Olivera et al 1990).…”
Section: Discussionsupporting
confidence: 91%
“…This is consistent with studies performed on other hymenopteran (wasp and bee) venoms (Argiolas and Pisano, 1985;Baptista-Saidemberg et al, 2011;Dias et al, 2014;Favreau et al, 2006;Gomes et al, 2014;Mendes et al, 2004;Qiu et al, 2012). Many of these linear peptides have antimicrobial properties and some possess additional insecticidal activity.…”
Section: Linear Peptidessupporting
confidence: 89%
“…[58] Hymenopteran venom peptides have not been extensively investigated to date. However, past studies on wasp venoms revealed small linear peptides [14,[59][60][61] and some rare single disulfide-linked peptides such as pallipine-I, ÀII and -III from the venom of the wasp Agelaia p. pallipes [14] and sylverin from the venom of Protonectarina sylveirae. [62] A wide survey of ant venom peptidomes has never been attempted before and this study therefore constitutes the most extensive overview conducted to date, providing a broad overview of the variability of ant venom peptide composition.…”
Section: Discussionmentioning
confidence: 99%